FLORAE MALESIANAE PRAECURSORES XIV* A REVISION OF THE GENUS DIPLYCOSIA (ERICACEAE) - H. SLEUMER (Reinwardtia, 1957)
In this revision of the nearly exclusively Malaysian genus Diplycosia Bl. 84 species and 12 varieties are distinguished, of which 17 new Malaysian species resp. 8 varieties and 2 extramalaysian species are described; 4 species have been reduced to varietal rank, 1 new name has been proposed. An index to specimens has been added.